Innovation in start-ups: Ideas filling the void or ideas devoid of resources and capabilities?. (July 2015) - Paradkar, Amit; Knight, John; Hansen, Paul
Abstract: We investigate how access to different types of resources affects the success of entrepreneurial start-up firms at early stages of development in small isolated economies by studying 12 start-ups based in New Zealand. We find that successful commercialization of innovations depends on the availability of complementary assets, and that capability-based resources, especially dynamic capabilities, have a greater impact on competitive advantage of start-ups than other intangible and tangible assets. For the start-ups in our study, alliances with partners are particularly important, and so the ability to form alliances is a key capability. Successful start-ups leverage their available resources to attract alliance partners in order to access necessary complementary resources. The start-ups in our study clearly demonstrated the ability to attract partners locally but struggled to do so internationally, thereby limiting their growth potential. Highlights: We identify types of resources most critical for success of start-up firms. Start-ups based in a small isolated economy face particular challenges. Successful commercialization depends on availability of complementary assets. Capability-based resources matter more than other intangible or tangible assets. Partnering with firms providing complementary assets is critical for survival.